2022
DOI: 10.1088/1361-6501/ac86e3
|View full text |Cite
|
Sign up to set email alerts
|

A self-adaptive DRSN-GPReLU for bearing fault diagnosis under variable working conditions

Abstract: Recently, deep learning has become an effective fault diagnosis method due to its no-mankind feature extraction capability. However, in real applications, rolling bearings are often used in the strong noise and variable working conditions, which lead to the degradation of fault diagnosis ability of neural network model. In order to solve the problem, a self-adaptive deep residual shrinkage network with global parametric rectifier linear unit (DRSN-GPReLU) is presented in this article for intelligent fault diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…(3) We propose a novel evaluation metric designed to measure the collective influence of diagnostic accuracy and computational complexity. In addition, it is experimentally demonstrated that the developed DRSN-CGPReLU can maintain a better diagnostic performance while greatly improving the diagnostic efficiency under variable operating conditions compared to our previous work [34].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…(3) We propose a novel evaluation metric designed to measure the collective influence of diagnostic accuracy and computational complexity. In addition, it is experimentally demonstrated that the developed DRSN-CGPReLU can maintain a better diagnostic performance while greatly improving the diagnostic efficiency under variable operating conditions compared to our previous work [34].…”
Section: Introductionmentioning
confidence: 85%
“…This innovative sub-network facilitates the autonomous creation of a suite of nonlinear transformations that take into account global features across diverse input signals. A visual representation of the sub-network's overall structure is provided in figure 1, while comprehensive details regarding its specific design are expounded in [34]. Nonetheless, in contrast to conventional ReLU and APReLU, the incorporation of an attention sub-network within GPReLU amplifies its operational efficacy, albeit at the expense of escalated computational intricacy.…”
Section: Our Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Song and Jiang [18] transformed the time series signals in the chemical process into matrix graphs and input them into multi-scale convolutional neural networks (MCNNs), realizing various fault diagnosis in the chemical production process, with a recognition accuracy of 88.54%. Some scholars have also improved CNN to improve the diagnostic effect of bearings [19,20]. Research has also found that CNN can effectively extract images generated by continuous wavelet transform (CWT) [21][22][23][24], and realize the diagnosis of different conditions in different fields.…”
Section: Introductionmentioning
confidence: 99%